Dynamics of Value Paradigms in Russian TV Content in 2002-2025 - Luiza G. Svitich (RUDN Journal of Studies in Literature and Journalism)
Presents the results of a sociological content-analytical study devoted to the dynamics of value paradigms based on the study of traditional values on Russian TV. The study was a panel study, that is, several times from 2002 to 2025, measurements of the values promoted by television were made according to a single codifier compiled on the basis of the analysis of 30 thousand folk proverbs collected by V.I. Dahl. Dynamics of the presentation of basic Russian values on the TV screen. Throughout the years under study, the television content actively reflected the creative potentials of the people, their optimism, desire for security and order. Over the years, the number of publications with the value of patriotism, mercy, philanthropy, peacefulness, love of truth, Orthodox spirituality, morality, conciliarity, and creativity has been increasing. And vice versa, there are fewer and fewer publications that promote consumer psychology, individualism, cruelty, egoism, immorality and other anti-values. The overall ratio of positive values and anti-values during this time changed from 58:42 to 83:17 %.